Os fatores que influenciam a implementação das boas práticas da governança corporativa nas empresas familiares - Santos, Ana Paula Azevedo de Holanda (2011)
This case study aims to investigate what are the factors that influence the implementation of good practices of corporate governance in family businesses. From a qualitative research approach, a single case study method was adopted. As research instrument, it was used semi-structured and opened interviews with members of the family owners representing the second and third generations, also representatives of the Board of Directors, active and non-active stakeholders. The content of the interviews was analysed for the processing of data. To support the research, there was the need of a literature review involving corporate governance; family businesses and their particularities; corporate governance in family businesses and the factors that influence and hinder the process of implementation of good corporate governance practices in the literature. The research presented here was held at the company Casa do Alemão Indústria e Comércio de Lanches LTDA which is from the foodstuff industry. It is under the command of the second and third generation of the founding family, having the second generation as dominant one. The results obtained in this survey pointed out that good corporate governance practices are partially present in the Organization and that for a full deployment, it is necessary to reformulate the elements already existing and the creation of new governance elements to improve the objectivity in the qualification, management, and succession. The factors considered as influential and positive for the full implementation of good corporate governance practices in this organization are: culture of transparency; separation of personal and company heritage; predisposition of all partners by accepting the use of more formal processes in the form of work. Among other reasons still not implemented and that could be influential elements for deployment are: need to deal with family conflicts; costs (investment); people's resistance (divergent interests of members, family, executives) and more monitoring (people don't like to be monitored and evaluated). Although load experience that time assigns to the founders, the company also demonstrates the agility of the youth to stay with a modern look and start a new policy of expansion.